2008
DOI: 10.1007/s00586-008-0816-5
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral pedicle stress fracture in a patient with osteoporotic compression fracture

Abstract: A case of bilateral pedicle stress fracture of L4 in a patient with osteoporotic compression fracture of L5 and without a history of major trauma or surgery is reported, and the literature is reviewed. Bilateral pedicle fracture is a rare entity and few cases have been reported in the literature. All reported cases had some underlying causative factors like previous spine surgery or stress related activities. To the best of the authors' knowledge, only one case of bilateral pedicle stress fracture without a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Bilateral pedicle stress fracture is a rare entity and we found that few cases have been reported in literature and underlying causative factors like previous spine surgery, spondylolysis or spondylolisthesis were described in these cases (2,(6)(7)(8)13). The pedicle may be exposed to increased forces after spine surgery, especially after spinal fusion, and the few pedicle stress fracture cases after surgery that occurred at the most proximal level of the fusion have been reported (3,9,12).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Bilateral pedicle stress fracture is a rare entity and we found that few cases have been reported in literature and underlying causative factors like previous spine surgery, spondylolysis or spondylolisthesis were described in these cases (2,(6)(7)(8)13). The pedicle may be exposed to increased forces after spine surgery, especially after spinal fusion, and the few pedicle stress fracture cases after surgery that occurred at the most proximal level of the fusion have been reported (3,9,12).…”
Section: Discussionmentioning
confidence: 82%
“…Bilateral multi-level pedicle fracture is an extremely rare condition and is generally associated with previous spine surgery or stress-related activities (2,6,7). We report a case of bilateral multi-level (four levels) pedicle fracture that was not associated with any obvious risk factors except bisphosphonate usage for osteoporosis.…”
Section: Introductionmentioning
confidence: 94%
“…There has been a case of stress fracture of both pedicles of L4 in a patient with osteoporotic compression fracture of L5 [7]. This patient had postmenopausal osteoporosis and did not have a history of major trauma or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In osteoporosis, the decreased vertebral body height can generate abnormal muscular stress. In addition, spinous processes show decreased elastic resistance [7]. Abnormal muscular stress on bones with decreased elastic resistance can result in fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral pedicle fracture of the vertebrae is uncommon and is especially rare without trauma or high velocity activity. Even more uncommon is neurologic deficit following these fractures [2]. Here we present a case of a 67year-old patient who presented with acute osteoporotic compression fracture of the lumbar 5 vertebra and bilateral pedicle fractures of the fourth and fifth lumbar vertebrae following an episode of coughing secondary to tracheitis.…”
Section: Introductionmentioning
confidence: 97%